(untitled) (Agro Productividad, 2024)
Objective: to characterize honey bee (Apis mellifera) production systems in the municipality of Hopelchén, Campeche, Mexico. Design/methodology/approach: the sample was made up by 10% of the beekeepers in Holpechén, identified through the snowball method. A semi-structured questionnaire was designed with 94 questions grouped into five sections (general information, structure of the systems, product trade, technologies used, and decision making). The questionnaire was applied through the technique of interviewing those responsible for the 118 beekeeping production systems. The information obtained with the questionnaires was analyzed with descriptive statistics. Results: beekeeping is an important productive activity in the region of Los Chenes and La Montaña in Hopelchén, which are undergoing the process of generational replacement and are currently maintained by young adult producers who are younger than 45 years old. They own 55 hives on average per producer, which are located at a distance of 7.7 km from their households. The main technology is the use of sugar for feed, by 50% of producers, followed by the diagnosis of Varroa infestation and determination of moisture with 35 and 21.5% of beekeepers. Limitations on study/implications: the limited access to regions with beekeeping potential, as well as the lack of monitoring by outside staff, does not ease open-mindedness of beekeepers toward researchers. Findings/conclusions: the characterization of beekeeping production systems with high potential allows proposing improvement strategies to promote the development of small-scale producers.